Reproductions of traditional discourse about women - Ruiz Dodobara, Rosa (2014)
The Critical Discourse Analysis is a relevant tool to elucidate everything that everyday discourse - apparently far from ideological interference - feed large sectors of the population. This time, it is a group that moves in contradiction: modern women - no matter how busy their new agendas are and how much “they have achieved in their struggle to have equal laborrights” - must continue playing their traditional roles of subordination to the male figure in order to respond to the image of “what she must be.”